Two independent approaches converge to the cloning of a new Leptosphaeria maculans avirulence effector gene, AvrLmS‐Lep2. (3rd March 2022) - Xiang Neik, Ting; Ghanbarnia, Kaveh; Ollivier, Bénédicte; Scheben, Armin; Severn‐Ellis, Anita; Larkan, Nicholas J.; Haddadi, Parham; Fernando, Dilantha W. G.; Rouxel, Thierry; Batley, Jacqueline; Borhan, Hossein M.; Balesdent, Marie‐Hélène
Abstract: Brassica napus (oilseed rape, canola) seedling resistance to Leptosphaeria maculans, the causal agent of blackleg (stem canker) disease, follows a gene‐for‐gene relationship. The avirulence genes AvrLmS and AvrLep2 were described to be perceived by the resistance genes RlmS and LepR2, respectively, present in B. napus 'Surpass 400'. Here we report cloning of AvrLmS and AvrLep2 using two independent methods. AvrLmS was cloned using combined in vitro crossing between avirulent and virulent isolates with sequencing of DNA bulks from avirulent or virulent progeny (bulked segregant sequencing). AvrLep2 was cloned using a biparental cross of avirulent and virulent L. maculans isolates and a classical map‐based cloning approach. Taking these two approaches independently, we found that AvrLmS and AvrLep2 are the same gene. Complementation of virulent isolates with this gene confirmed its role in inducing resistance on Surpass 400, Topas‐ LepR2, and an RlmS ‐line. The gene, renamed AvrLmS‐Lep2, encodes a small cysteine‐rich protein of unknown function with an N‐terminal secretory signal peptide, which is a common feature of the majority of effectors from extracellular fungal plant pathogens. The AvrLmS‐Lep2 / LepR2 interaction phenotype was found to vary from a typical hypersensitive response through intermediate resistance sometimes towards susceptibility, depending on the inoculation conditions. AvrLmS‐Lep2 was nevertheless sufficient to significantly slow the systemic growth of the pathogen and reduce the stem lesion size on plant genotypes with LepR2, indicating the potential efficiency of this resistance to control the disease in the field. Abstract : AvrLmS‐Lep2, the 10th cloned Leptosphaeria maculans AVR gene, was easily identified by bulk sequencing, and induces a fluctuating phenotype on rapeseed cotyledons that nevertheless limits stem canker severity.